Decline in human sperm parameters: How to stop? - Elnashar, Aboubakr Mohamed (Clinical Journal of Obstetrics and Gynecology, 2023)
A large systematic review and meta-regression analysis found that sperm counts all over the world appeared to be declining rather than stabilizing. The decline in male sperm counts does not necessarily translate to a decline in male fertility. The cause of declining sperm counts remains unknown; however, several potential causative factors have been identified: 1. Chronic diseases: diabetes mellitus, hypertension; hyperlipidemia, hyperuricemia and skin Diseases & metabolic syndrome. 2. Environmental factors: bisphenol a; phthalates; heavy metals and heat. 3. Lifestyle: obesity, diet, tobacco, alcohol, marijuana, stress, reduced sleep & sedentary life. Addressing these causes is required to stop or decrease male fertility decline. Action to improve semen quality such as prevention & treatment of chronic disease, decreasing unhealthy lifestyle behaviors such as smoking, poor diet, or lack of physical activity & eliminating toxic environmental chemicals.